A study on the influence of organizational climate towards knowledge sharing behaviour: a case study of Yayasan Sarawak / Dayangku Nurdayana Lee Awang Jidel and Nur Hanisah Mohd Ali @ Zam - Awang Jidel, Dayangku Nurdayana; Mohd Ali @ Zam, Nur Hanisah (2018)
This chapter focuses on the background of the study which is in determining organizational climate as the factor contributing to the behavioural of Yayasan Sarawak’s employees in knowledge sharing. The presentation of the chapter begins with the research background, followed by the problem statement, research questions, research objectives, scope of study, significant of the study and lastly the definition of terms and concepts used in this study. Knowledge is regarded as the most strategically crucial sources and wealth (Conner and Prahalad, 1996). The sharing of knowledge between individuals and sections in an organization is the most process (Osterloh and Frey, 2000). As mentioned by Senge (1998), when an individual is willing to facilitate as well as to learn from others in the new development of competencies, knowledge sharing can be occurred. To Sveiby’s (2001) argues that when the knowledge flows in and out among the individual, their competencies, skills and abilities will increase as well as they can be creating new knowledge. The organizational climate in the organization is significant to the behaviour sharing of knowledge among the employees as it facilitates the cooperative work and a well-functioning organization.